2016
DOI: 10.1364/oe.24.012600
|View full text |Cite
|
Sign up to set email alerts
|

06-32 μm supercontinuum generation in a step-index germania-core fiber using a 44 kW peak-power pump laser

Abstract: An ultra-broadband supercontinuum was generated in a short piece of step-index germania-core fiber using a fiber laser with a peak power of 4.4 kW. The pure germania core made this fiber capable of propagating light towards the desirable mid-infrared region. The spectral broadening characteristics towards the mid-infrared region under different lengths of germania-core fiber were investigated using pump pulses of 4.4 kW and 1.1 ns at 1550 nm. The large nonlinear refractive index of germania and the small core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…A pump source near 1550 nm has led to spectral broadening towards visible wavelength, on the contrary a pump source near 2000 nm limits broadening towards blue wavelength to 1700 nm [15,[17][18][19]. The measured ZDW of GeO 2 glass is around 1.73-1.74 μm, however for a GeO 2 doped fiber, the ZDW will depend on the exact concentration of GeO 2 (as it decides NA of fiber as well) and core diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pump source near 1550 nm has led to spectral broadening towards visible wavelength, on the contrary a pump source near 2000 nm limits broadening towards blue wavelength to 1700 nm [15,[17][18][19]. The measured ZDW of GeO 2 glass is around 1.73-1.74 μm, however for a GeO 2 doped fiber, the ZDW will depend on the exact concentration of GeO 2 (as it decides NA of fiber as well) and core diameter.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, a pure GeO 2 doped fiber with 9 μm core diameter was used and the obtained spectrum suffered from a broad OH absorption peak around 2700 nm. In 2016 Yang et al demonstrated an SC with a 10dB bandwidth of 717 nm to 2998 nm, with a total of 450 mW output power [19]. A pure GeO 2 core fiber of 3 μm core diameter was used.…”
Section: Introductionmentioning
confidence: 99%
“…Various supercontinuum (SC) generated highly nonlinear photonic crystal fibers (HN-PCFs) have been reported in the literature for optical communications and medical applications [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], using different materials to produce broadband SC spectrum with varying performances.…”
Section: Introductionmentioning
confidence: 99%
“…Different designs of femtosecond (fs), picosecend and nanosecond pulse laser sources are proposed and consequently, investigated in references [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In [10], the authors investigate the performance of femtosecond-laser pulses in neodymium-doped yttrium aluminium garnet (Nd:YAG) crystals and report that output power of around 1.3 W at around 1.0 µm center wavelength is achievable from an 2.25 W launched pump power.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attempts of SC generation in highly doped GeO 2 fiber involve a 2 μm laser as a pump source, which limits the blue edge of the spectrum above 1.7 μm [2]. Recently, Yang et al claimed a pure Germania core fiber with a 1.426 μm ZDW and demonstrated a 10 dB bandwidth from 717 nm to 2998 nm but output power was limited to 350 mW [3]. In this paper, we report a SC based on a 74 mol % GeO 2 doped core fiber, which is being pumped by a broadband 4-stage Er-Yb fiber based master oscillator power amplifier (MOPA).…”
Section: Introductionmentioning
confidence: 99%